Crosslinked polyolefin foam and process for producing same
Patent Information
- Application Number
- JP2022538355
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-12-26
- Filing Date
- 2020-12-02
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2040-12-02
AI Technical Summary
Existing methods for producing crosslinked polyolefin foams face challenges such as narrow foaming temperature ranges, high costs, and the need for chemical blowing agents, which are economically unfavorable and require additional processing steps like sauna or hot water curing.
A process using silane-functionalized polyolefins with a silanol condensation catalyst under controlled extrusion conditions, allowing for a wide foaming temperature range and moisture curing without sauna or hot water treatment, forming crosslinked foams with varying densities and cell structures.
Enables efficient production of crosslinked foams with a broad temperature range, reducing costs and eliminating the need for high-temperature post-extrusion processing, while achieving desired density and cell structure properties.
Abstract
Description
[Background technology]
[0001] Low-density polyolefin foams have a foam density of less than approximately 200 kilograms / cubic meter (less than 0.200 g / cc) and can be crosslinked or uncrosslinked. Crosslinked foams generally have superior physical properties (e.g., higher compression set and heat resistance) compared to uncrosslinked foams. Crosslinked foams can also be produced in batch processes as either open-cell or closed-cell foams. However, batch processes used to produce crosslinked foams are often economically undesirable and require expensive chemical blowing agents.
[0002] Non-crosslinked polyolefin foams are typically produced by (i) continuous extrusion processes, (ii) higher production rates, and (iii) more economical than batch processes. Extrusion uses physical blowing agents, which are less expensive than chemical blowing agents. However, the abrupt change in the melt viscosity of semi-crystalline polyolefins around their melt temperature results in a narrow foaming temperature range that can be used in extrusion, thereby limiting the use of extrusion processes for the production of polyolefin foams.
[0003] Free radical generators (e.g., peroxides, radiation) are typically used to achieve crosslinking of polyolefins. However, peroxides are unsuitable for the extrusion foaming process because (ii) the extrusion of peroxide-containing polymer compositions must be carried out at a low melting temperature to avoid premature crosslinking in the extruder, and (ii) an additional vulcanization step at high temperatures after extrusion is required to decompose the peroxides and crosslink the polymer. Radiation can be used to crosslink extruded foams after they come out of the die, but the radiation crosslinking process is expensive and only useful for relatively thin foams due to its limited penetration depth.
[0004] Furthermore, moisture-inducible crosslinking of extruded foams made from alkoxysilane-functionalized polyolefins is also known. However, moisture-inducible crosslinking of alkoxysilane-functionalized polyolefin extruded foams as taught in the prior art is disadvantageous due to the low effectiveness of the silanol condensation catalyst and the essential post-extrusion moisture treatment process at high temperatures and humidity in a sauna or hot water bath.
[0005] The technical field recognizes the need for an extrusion process for producing cross-linked foams that allows for a wide foaming temperature range, is efficient and cost-effective, and enables the formation of open-cell and / or closed-cell foams, without requiring post-extrusion treatment steps at high temperatures and humidity, such as curing in a sauna and / or in a hot water bath. [Overview of the project]
[0006] This disclosure relates to a process for producing a crosslinked foam, which provides a wide (±10°C) range of foaming temperature. This process avoids free radical crosslinking (without peroxides) and utilizes alkoxysilane-functionalized polyolefins, and this process also avoids moisture curing in a sauna and / or curing in a hot water bath.
[0007] This disclosure provides a process. In one embodiment, the process includes providing an extruder and a polymer composition under extrusion conditions at a temperature of 50°C to 250°C. The polymer composition comprises (A) 5% by weight or more of a silane-functionalized olefin polymer having a first melt temperature, Tm1; (B) optionally a non-silane-functionalized polyolefin having a second melt temperature, Tm2; (C) a highly effective silanol condensation catalyst (HEC); (D) a permeability modifier; and (E) optionally a scorch inhibitor. The process includes introducing a physical blowing agent into the polymer composition under extrusion conditions to form a foamed composition. The process includes cooling the foamed composition to a foaming temperature of less than 10°C to more than 10°C, Tm1, and pushing the foamed composition out of the outlet die of the extruder to form a foamed composition. This process involves moisture curing a foam composition to form a cross-linked foam composition having a density of 0.010 grams per cubic centimeter (g / cc) to 0.200 g / cc and a gel content of 5% to 100%. definition
[0008] All references to the Periodic Table of Elements in this specification refer to the Periodic Table of Elements published and copyrighted by CRC Press, Inc. in 2003. Any reference to a group(s) refers to the group(s) as they appear in the Periodic Table using the IUPAC system for numbering groups. Unless otherwise stated, suggested by the context, or customary in the art, all parts and percentages are based on weight. For the purposes of U.S. patent practice, any patent, patent application, or publication referenced herein is incorporated herein in its entirety by reference (or its equivalent U.S. edition is incorporated by reference).
[0009] Numerical ranges disclosed herein include all values from the lower limit to the upper limit (including boundary values). In the case of a range that includes an explicit value (e.g., the range of 1 or 2, or 3 to 5, or 6 or 7), any subrange between two explicit values is included (e.g., the above range 1 to 7 includes subranges 1 to 2, 2 to 6, 5 to 7, 3 to 7, 5 to 6, etc.).
[0010] Unless otherwise stated, unless implicitly stated in the context, or unless customary in the art, all parts and percentages are based on weight, and all test methods are current as of the filing date of this disclosure.
[0011] As used herein, the term “ambient conditions” refers to a temperature of 10°C to 35°C (room temperature), a pressure of 0.95 to 1.05 atmospheres, or 1 atmosphere.
[0012] As used herein, the term “composition” refers to a mixture of materials comprising the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0013] The terms “comprising,” “including,” and “having,” and their derivatives, are not intended to exclude the existence of any additional components, processes, or procedures, whether or not they are specifically disclosed. To avoid any doubt, all compositions claimed through the use of the term “comprising” may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless otherwise stated. In contrast, the term “essentially consisting of” excludes any other components, processes, or procedures from the scope of any subsequent description, except those not essential to operability. The term “consisting of” excludes any components, processes, or procedures not specifically described or listed.
[0014] As used herein, the term "bubble density" refers to the number of foam bubbles in a unit volume of a foam composition.
[0015] As used herein, the term "blowing nucleating agent" is a compound or composition that provides sites for the growth of foam cells.
[0016] As used herein, the term "closed-cell foam" is a foam in which the foam cells are separated by the film walls of the polymeric material that do not have openings and the closed-cell volume is not readily in fluid communication with its external atmosphere. As used herein, the term "open-cell foam" is one in which (i) there are no film walls of polymeric material separating the foam cells or (ii) there are openings in the film walls of the polymeric material and the open-cell volume is in fluid communication with its external atmosphere.
[0017] As used herein, "ethylene-based polymer" or "ethylenic polymer" is a polymer that contains greater than 50 weight percent, based on the total amount of polymerizable monomers, of polymerized ethylene monomers and optionally may contain at least one comonomer.
[0018] As used herein, the term "foam" or "foam composition" is a structure composed of a polymer and the structure includes a plurality of channels that extend from the surface of the structure into and through the structure. The channels are non-directional with respect to the longitudinal extension of the structure and the channels include a plurality of foam cells that are in fluid communication with the external atmosphere. As used herein, the term "foam cell" or "cell" is a discrete space within the foam composition and the foam cells are separated by a film wall that includes the polymer of the foam composition or otherwise defined.
[0019] As used herein, the term "foam collapse" is a foamable composition that cannot expand sufficiently when passing through a die at the foaming temperature used.
[0020] As used herein, the term “freeze off” refers to a semi-crystalline polyolefin that solidifies in a section of the extrusion foaming process used to cool a foaming composition, thereby impairing heat transfer and the melting temperature at or immediately before the start of die expansion (and / or “foam collapse”).
[0021] The term "foaming temperature" refers to the final set temperature in the foam extruder or other suitable heat exchanger, cooling section, or cooling section of another suitable heat exchanger located immediately upstream of the outlet die. For example, the foaming temperature may be the set temperature in the last zone of an extruder used to cool the foaming composition. The set temperature may or may not be different from the melting temperature of the extruder (foaming composition) measured at the outlet die.
[0022] As used herein, “olefin polymer” or “polyolefin” is a polymer containing more than 50 weight percent (based on the total amount of polymerizable monomers) of polymerizable olefin monomers and optionally containing at least one comonomer. Non-limiting examples of olefin polymers include ethylene polymers (ethylenically active polymers) and propylene polymers.
[0023] A "polymer" is a compound prepared by polymerizing monomers, whether of the same or different types, and is a compound that, in its polymeric form, provides multiple and / or repeating "units" or "structural units" that make up the polymer. Therefore, the general term polymer encompasses the term homopolymer and is usually used to refer to polymers prepared from only one type of monomer, while the term copolymer is usually used to refer to polymers prepared from at least two types of monomers. It also encompasses all forms of copolymers, such as random and block. The terms "ethylene / α-olefin polymer" and "propylene / α-olefin polymer" refer to the aforementioned copolymers and one or more additional polymerizable α-olefin monomers prepared by polymerizing ethylene or propylene, respectively. Polymers are often referred to as being "made from" one or more specified monomers, such as "based on" a specified monomer or type of monomer, or "containing" a specified monomer content, but it should be noted that in this context, the term "monomer" is understood to refer to the polymerization residue of a specified monomer and does not refer to non-polymerized species. Generally, polymers in this specification are referred to as "units" that are the polymerization forms of the corresponding monomers. Test method
[0024] As used herein, the terms “bubble count” or “average bubble count” refer to the number of bubble wall intersections over a specified length. The bubble count of a foam composition is measured over a specified length by taking up to 10 measurements for each foam sample and calculating the average per specified length (i.e., “average bubble count”).
[0025] As used herein, the terms “bubble diameter” or “average bubble diameter” are measures of the dimensions of foam bubbles. Bubble diameter is determined by dividing the average number of bubbles by a given length and multiplying the result by 1.62, which is an established geometric factor for this purpose disclosed in Cellular Polymers, Vol, 21, No. 3, 165-194 (2002). Bubble diameter (i.e., average bubble diameter) is measured according to ASTM D3576-77 and reported in millimeters (mm).
[0026] The density of the foam composition was measured according to ASTM D-1622-88, and the result was kilograms per cubic meter (kg / m³) at 25°C. 3 ) or reported in grams per cubic centimeter (g / cc).
[0027] The polymer density is measured according to ASTM D792, and the results are reported in g / cc at 25°C.
[0028] The gel content of the foam composition is measured by extraction with decahydronaphthalene (decalin) according to ASTM D2765-16 Method C, and the results are reported as weight percent. Instead of the powder test specimens typically used when this test is performed on polymers, thin slices of foam specimens are used for this test.
[0029] The melt index (MI or I2) is measured according to ASTM D 1238, under conditions of 190°C / 2.16 kg, and the results are reported in grams per 10 minutes (g / 10 min).
[0030] The melting temperature, or Tm, is measured by DSC (Differential Scanning Calorimetry) technique and refers to the peak melting point of a semi-crystalline polyolefin as measured in U.S. Patent No. 5,783,638. It should be noted that many blends containing two or more polyolefins have more than one melting temperature, while many individual polyolefins have only one melting temperature.
[0031] The open-cell content of the foam composition is measured according to ASTM D2856-94 and reported as a percentage from 0% to 100%. The open-cell content is also measured from the penetration height of the red water when the foam test specimen is immersed in a beaker containing red water. The procedure is as follows: (a) cut the foam sample into 100 mm long pieces; (b) mark a line 50 mm from one end of each test specimen; (c) immerse the foam sample in a beaker of red water, maintaining a constant length of 50 mm below the water surface for a constant time of 1 minute; (d) remove the foam test specimen from the water and wipe off any surface liquid; (e) slice the foam in half along its length using a blade; (f) examine the inner surface of the foam test specimen revealed by slicing to determine how far the water penetrated. The greater the penetration height of the colored water, the greater the open-cell content (as a qualitative measurement). [Modes for carrying out the invention]
[0032] This disclosure provides a process. In one embodiment, the process includes providing an extruder and a polymer composition under extrusion conditions at a temperature of 50°C to 250°C. The polymer composition comprises (A) a silane-functionalized olefin polymer having a first melt temperature, Tm1, in an amount of 5% by weight or more; (B) optionally a non-silane-functionalized polyolefin having a second melt temperature, Tm2; (C) a high-efficiency silanol condensation catalyst (HEC); (D) a permeability modifier; and (E) optionally a scorch inhibitor. The process includes introducing a physical blowing agent into the polymer composition under extrusion conditions to form a foamed composition. The process includes cooling the foamed composition to a foaming temperature of less than 10°C to more than 10°C, which is Tm1. This process includes pushing a foaming composition out of the outlet die of an extruder to form a foam composition, and moisture-curing the foam composition to form a cross-linked foam composition having a density of 0.010 grams / cubic centimeter (g / cc) to 0.200 g / cc and a gel content of 5% to 100%. A. Silane-functionalized olefin polymers
[0033] This process involves providing a silane-functionalized olefin-based polymer (or silane-functionalized olefin-based polymer, "Si-f-PO"). Si-f-PO may be a silane-functionalized propylene-based polymer (Si-f-PP) or a silane-functionalized ethylene-based polymer (Si-f-PE). Si-f-PO has a melting temperature, or a first melting temperature, Tm1.
[0034] In embodiments, Si-f-PO is a silane-functionalized ethylene polymer (Si-f-PE) which is a reactor ethylene / silane copolymer. The ethylene / silane copolymer is prepared from ethylene monomers and alkoxysilane comonomers, and optionally one or more other copolymerizable monomers (such as vinyl acetate or ethyl acrylate) copolymerized in the polymerization reactor. The polymerization reactor used to produce the reactor ethylene / silane copolymer may be a high-pressure reactor (but is not limited to). As used herein, the term “high-pressure reactor” means a polymerization reactor operating at a pressure of at least 34.47 megapascals (mPa) (5000 pounds per square inch (psi)).
[0035] In one embodiment, the silane-functionalized ethylene polymer is a silane-grafted ethylenic polymer. As used herein, the term "silane-grafted ethylenic polymer" refers to an alkylsiloxyethylene polymer prepared by post-reactoral grafting of an alkoxysilane into an ethylenic polymer. In one embodiment, the alkoxysilane is grafted into the ethylenic polymer in the presence of a free radical initiator.
[0036] Ethylene-based polymers are produced using conventional polyethylene polymerization techniques, such as high pressure, Ziegler-Natta, metallocene, or geometrically constrained catalysts. In one embodiment, polyethylene is produced in a high-pressure reactor. In further embodiments, polyethylene is produced in solution, slurry, or gas-phase polymerization processes using mono- or bis-cyclopentadienyl, indenyl, or fluorenyl transition metal catalysts or geometrically constrained catalysts in combination with activators. U.S. Patent No. 5,064,802, International Publication Nos. 93 / 19104 and 95 / 00526 disclose geometrically constrained metal complexes and methods for preparing them. International Publication Nos. 95 / 14024 and 98 / 49212 disclose substituted indenyls containing geometrically constrained metal complexes and methods for preparing them.
[0037] In one embodiment, the ethylenic polymer is a product of post-reactoral modification, such as reactive extrusion, for producing a graft copolymer.
[0038] In one embodiment, the ethylenic polymer may be branched, linear, or substantially linear. As used herein, the term “branched ethylenic polymer” refers to an ethylenic polymer prepared in a high-pressure reactor having a highly branched polymer structure, where branching is observed both on the polymer backbone and in the branches themselves. As used herein, the term “substantially linear ethylenic polymer” refers to an ethylenic polymer having a backbone substituted with 0.01 to 3 long-chain branches per 1,000 carbon atoms. In one embodiment, the ethylenic polymer may have a backbone substituted with 0.01 to 1 long-chain branch per 1,000 carbon atoms, or 0.05 to 1 long-chain branch per 1,000 carbon atoms.
[0039] In one embodiment, the ethylenic polymer is a homopolymer, an interpolymer, a random or block copolymer, a functionalized polymer (e.g., ethylene vinyl acetate, ethylene ethyl acrylate, etc.), or a non-functionalized polymer. In further embodiments, the ethylenic interpolymer is an elastomer, a flexomer, or a plastomer.
[0040] In one embodiment, the ethylenic polymer is an ethylene / α-olefin copolymer. The α-olefin is C3-C 20 Examples include linear, branched, or cyclic α-olefins, or C4-C8 linear α-olefins. 20Non-limiting examples of α-olefins include propene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, and 1-octadecene. α-olefins have a cyclic structure such as cyclohexane or cyclopentane, and can yield α-olefins such as 3-cyclohexyl-1-propene (allylcyclohexane) and vinylcyclohexane. Non-limiting examples of C4-C8 linear α-olefins include 1-butene, 1-hexene, and 1-octene.
[0041] Non-limiting examples of ethylenic polymers include high-density polyethylene (HDPE), medium-density polyethylene (MDPE), linear low-density polyethylene (LLDPE), low-density polyethylene (LDPE), very low-density polyethylene (VLDPE), uniformly branched, linear ethylene / α-olefin copolymers (e.g., TAFMER® by Mitsui Petrochemicals Company Limited and EXACT® by DEX Plastomers), uniformly branched, substantially linear ethylene / α-olefin polymers (e.g., AFFINITY® polyolefin plastomers and ENGAGE® polyolefin elastomers available from The Dow Chemical Company), and ethylene block copolymers (INFUSE® available from The Dow Chemical Company). Substantially linear ethylene copolymers are described in U.S. Patents No. 5,272,236, 5,278,272, and 5,986,028, while ethylene block copolymers are described in U.S. Patents No. 7,579,408, 7,355,089, 7,524,911, 7,514,517, 7,582,716, and 7,504,347.
[0042] In one embodiment, the ethylenic polymer includes units derived from ethylene in an amount of 50, 60, 80, 85 to 90, 95, 97, 99, 99.5, or 100 weight percent (wt%). In a further embodiment, the ethylenic polymer includes units derived from ethylene in an amount of 50 to 100 wt%, or 60 to 99.5 wt%, or 80 to 95 wt%.
[0043] In one embodiment, the ethylenic polymer is an ethylene / α-olefin interpolymer having an α-olefin content of 15, 20, 25 to 40, 45, or 50% by weight, based on the weight of the interpolymer. In a further embodiment, the ethylenic polymer is an ethylene / α-olefin copolymer having an α-olefin content of 15-50% by weight, 20-45% by weight, or 25-40% by weight, based on the weight of the interpolymer. The α-olefin content is determined using the procedure described in Randall (Rev. Macromol. Chem. Phys., C29(2&3)) 13 It can be measured by 13C nuclear magnetic resonance (NMR) spectroscopy.
[0044] In one embodiment, the ethylenic polymer has a melt index (I2) of 0.1, 0.5, 1-2, 5, 10, 20, 30, or 50 g / 10 min. In a further embodiment, the ethylenic polymer has a melt index (I2) of 0.1-50 g / 10 min, 0.5-30 g / 10 min, or 1-5 g / 10 min.
[0045] In one embodiment, the ethylenic polymer does not contain styrene-based polymers (e.g., styrene, methylstyrene) or is excluded by other means.
[0046] The ethylenic polymer may consist of two or more embodiments disclosed herein.
[0047] As used herein, the terms “alkoxysilane” or “alkoxysilane monomer” refer to an alkoxysilane that is grafted onto an ethylenic polymer or copolymerized with an ethylene monomer. An alkoxysilane or alkoxysilane monomer has a structure represented by the following formula: [ka] In the formula, R 1 is a hydrogen atom or a methyl group, x and y are either 0 or 1, provided that when x is 1, y is also 1. n is an integer between 1 and 12. Each R'' is independently a hydrolyzable organic group.
[0048] In one embodiment, each R'' is independently an alkoxy group having 1 to 12 carbon atoms (e.g., methoxy, ethoxy, butoxy), an aryloxy group (e.g., phenoxy), an araloxy group (e.g., benzyloxy), an aliphatic acyloxy group having 1 to 12 carbon atoms (e.g., formyloxy, acetyloxy, propanoyloxy), an amino or substituted amino group (e.g., alkylamino, arylamino), or a lower alkyl group having 1 to 6 carbon atoms, where one or less of the three R'' groups are alkyl.
[0049] In one embodiment, the alkoxysilane is an unsaturated silane having an ethylenically unsaturated hydrocarbyl group (e.g., vinyl, allyl, isopropenyl, butenyl, cyclohexenyl, or gamma-(meth)acrylooxyallyl group) and a hydrolyzable group (e.g., hydrocarbyloxy, hydrocarbonyloxy, or hydrocarbylamino group). Non-limiting examples of hydrolyzable groups include methoxy, ethoxy, formyloxy, acetoxy, propionyloxy, alkyl, and arylamino groups. In further embodiments, alkoxysilanes and methods for preparing the same are described in U.S. Patent No. 5,266,627 (Meverden et al.).
[0050] In one embodiment, the alkoxysilane is selected from vinyl trimethoxysilane (VTMS), vinyl triethoxysilane (VTES), vinyl triacetoxysilane, gamma-(meth)acrylooxypropyltrimethoxysilane, or a combination thereof.
[0051] In one embodiment, the alkoxysilane is vinyltrimethoxysilane (VTMS) and / or vinyltriethoxysilane (VTES).
[0052] The alkoxysilane may consist of two or more embodiments disclosed herein.
[0053] In one embodiment, the silane-functionalized ethylene polymer (Si-f-PE) is a reactor ethylene / silane copolymer containing units derived from ethylene monomers and alkoxysilane monomers. The reactor ethylene / silane copolymer consists of units derived from ethylene monomers and alkoxysilane monomers as the sole monomers. Alternatively, the ethylene / silane copolymer further includes units derived from one or more monomers other than ethylene monomers and alkoxysilane monomers. In one embodiment, the ethylene / silane copolymer does not contain or excludes units derived from styrene monomers (e.g., styrene, methylstyrene).
[0054] In one embodiment, Si-f-PE comprises VTMS and / or VTES comonomers and has one, some, or all of the following properties: (i) Melting temperature Tm1, Tm1, from 50°C, or 60°C, or 70°C, or 80°C, or 90°C, or 100°C, or 103°C, or 105°C, or 108°C to 110°C, or 111°C, or 112°C, or 113°C, or 114°C, or 115°C, or 116°C, or 120°C, or 130°C, or 140°C, and / or (ii) Melt index (I2) of 0.3, or 0.5, or 1.0, or 1.3 to 1.7, or 2.0, or 3.0, or up to 10 g / 10 min, and / or (iii) densities of 0.860, or 0.880, or 0.900, or 0.910, or 0.913, or 0.916, or 0.920 to 0.925, or 0.930, or 0.950, or 0.980, or 1.0, or 1.3, or 1.4 g / cc, and / or (iv) VTMS content up to 0.1, 0.3, 0.5, 0.8, 1.0, 1.3 to 1.7, 1.9, 2.3, 3.0, 5, or 10% by weight, based on the total weight of Si-f-PE, and / or (v) A polydispersity index (PDI or Mw / Mn) ranging from 1.7, or 2.0, 3.0, or 3.5, or 4.0, or 4.5, or 5.0, or 5.3 to 5.7, or 6, or 8, or 10, or 20.
[0055] In one embodiment, Si-f-PE is a reactor ethylene / silane copolymer consisting only of units derived from ethylene monomer and VTMS comonomer, and having one, some, or all of the following properties: (i) Melting temperature, Tm1, of 95°C to 140°C, or 100°C to 130°C, or 105°C to 115°C, or 106°C to 112°C, or 108°C to 110°C, and / or (ii) Melt index (I2) of 0.5-3 g / 10 min, or 1-2 g / 10 min, or 1.3-1.7 g / 10 min, and / or (iii) Densities of 0.900 to 0.970 g / cc, or 0.910 to 0.940 g / cc, or 0.913 to 0.930 g / cc, or 0.915 to 0.925 g / cc, and / or (iv) VTMS content of 0.3–5% by weight, or 1.0–2.0% by weight, or 1.3–1.7% by weight, based on the total weight of the ethylene / silane copolymer, and / or (v) A multivariance index (PDI or Mw / Mn) between 1.7 and 20.0, or 2.0 and 10.0, or 3.0 and 8.0, or 4.0 and 6.0, or 5.3 and 5.7.
[0056] In one embodiment, Si-f-PO is Si-g-PE and is present in an amount exceeding 50% by weight based on the total weight of the polymer composition.
[0057] In one embodiment, Si-f-PO is Si-g-PE and is present in amounts up to 1, 3, 5, 7, 9, 11, 20, 30, 40, 50, 60, 70, 80 to 85, 90, 93, 95, 97, 99, or 99.9% by weight, based on the total weight of the polymer composition. In further embodiments, Si-f-PE is present in amounts up to 1-99.9% by weight, or 5-99% by weight, or 9-95% by weight, or 30-93% by weight, or 50-99% by weight, or 70-95% by weight, or 80-93% by weight, or 89-95% by weight, or 5-50% by weight, or 5-30% by weight, or 5-20% by weight, or 5-15% by weight, or 5-11% by weight, based on the total weight of the polymer composition.
[0058] The silane-functionalized olefin polymer may consist of two or more embodiments disclosed herein. B. Non-silane-functionalized polyolefins
[0059] The process comprises providing an optional non-silane-functionalized polyolefin, component (B). If present, the non-silane-functionalized polyolefin is an ethylene-based polymer or a propylene-based polymer that does not contain silane functional groups, as described above herein. In other words, the non-silane-functionalized polyolefin does not contain alkoxysilanes and does not contain alkoxysilane monomers. The non-silane-functionalized polyolefin has a melting temperature, a second melting temperature Tm2. In other words, to distinguish the melting temperatures of component (A) and component (B), the silane-functionalized olefin polymer (A) has a melting temperature indicated as a first melting temperature, or Tm1, and the non-silane-functionalized polyolefin (B) has a melting temperature indicated as a second melting temperature, or Tm2.
[0060] In one embodiment, the non-silane-functionalized polyolefin is low-density polyethylene (LDPE). The LDPE has a density of 0.900, 0.910, 0.920 to 0.930, or 0.940 g / cc. In a further embodiment, the LDPE has a density of 0.910 to 0.930 g / cc, 0.913 to 0.928 g / cc, or 0.915 to 0.925 g / cc.
[0061] In one embodiment, the LDPE has a melt index (I2) of 0.1, or 0.5 to 1.0, or 2.0, or 3.0, or 5.0, or 10, or 20, or 30, or 50 g / 10 min. In a further embodiment, the LDPE has a melt index (I2) of 0.1 to 10.0 g / 10 min, or 0.5 to 5.0 g / 10 min, or 1.0 to 3.0 g / 10 min.
[0062] In one embodiment, the LDPE has a melting temperature (Tm2) of 100°C, or 103°C, or 106°C, or 108°C to 110°C, or 111°C, or 112°C, or 114°C, or 116°C, or 118°C, or 120°C. In a further embodiment, the LDPE has a melting temperature (Tm2) of 106°C to 114°C, or 108°C to 112°C.
[0063] In one embodiment, LDPE is present in an amount of 0, greater than 0, or 1, 3, 5, 7, 9, 11, 20, 30, 40, 50, 80 to 90, 93, 95, or 99% by weight, based on the total weight of the polymer composition. In a further embodiment, LDPE is present in an amount of 1 to 99% by weight, or 1 to 95% by weight, or 5 to 93% by weight, or 10 to 90% by weight, or 20 to 80% by weight, or 50 to 95% by weight, or 80 to 90% by weight, or 89 to 95% by weight, based on the total weight of the polymer composition.
[0064] In one embodiment, LDPE has one, some, or all of the following characteristics: (i) Melting temperature, Tm2, of 105°C to 120°C, or 107°C to 115°C, or 108°C to 112°C, and / or (ii) Melt index (I2) of 0.5-5.0 g / 10 min or 1.0-3.0 g / 10 min, and / or (iii) Density of 0.910 to 0.930 g / cc or 0.915 to 0.925 g / cc.
[0065] LDPE (non-silane-functionalized polyolefin) may consist of two or more embodiments disclosed herein.
[0066] In one embodiment, the polymer composition does not contain any non-silane-functionalized polyolefins. C. High-efficiency silanol condensation catalyst
[0067] This process involves providing a highly efficient silanol condensation catalyst (HEC). The terms "highly efficient silanol condensation catalyst" or "HEC" refer to a catalyst other than dibutyltin dilaurate (DBTDL) (or otherwise a catalyst that is not DBTDL) that, when measured in days to 100% high-temperature creep or 80% high-temperature creep (150°C or 200°C, 0.2 MPa), yields crosslinking (moisture curing) at 23°C and 50% relative humidity with the same filler weight (of an extruded tape of a given thickness in the range of 1.3-1.8 mm, made from unfoamed Si-f-PO).
[0068] The degree of hardening (crosslinking) is determined by measuring hot-set creep (also known as hot-set elongation or HSE). The test is based on the Insulated Cable Engineers Association ICEA-T-28-562-2003 standard for power cable insulation materials. Test specimens are taken from tapes with thickness values ranging from 0.8 mm to 2.0 mm along the extrusion direction. Three test specimens of each sample are cut using an ASTM D412 type D tensile bar (dumbbell). A hot-set creep test is performed on the specimens (of the measured thickness value) in an oven with a glass door set to 150°C or 200°C with a stress of 0.2 MPa applied to the bottom of the specimens. The specimens are fixed vertically from the top of the oven, and a load is applied to the bottom of each specimen. The specimens are subjected to the hot-set creep test at either 150°C or 200°C for 15 minutes, and the rate of increase in length is measured at time intervals. The average of the three measurements (rate of increase in length) is reported as "hot-set creep" or HSE.
[0069] The term "crosslinking (moisture curing) that is 1.5 times faster than DBTDL at the same loading" means that, for example, when the fixed loading of DBTDL alone in an extruded tape test piece of a given thickness (unfoamed) made from fixed Si-f-PO (or Si-f-PE) requires 18 days to achieve 100% high temperature creep or 24 days to achieve 80% high temperature creep (when cured at 23 °C and 50% relative humidity), using the same loading of HEC instead of DBTDL alone enables 100% high temperature creep to be achieved in 12 days or less or 80% high temperature creep to be achieved in 16 days or less under the same curing conditions.
[0070] Typical curing data using a 1.5 mm thick (unfoamed) extruded tape test piece made from SI-LINK (trademark) AC DFDB-5451NT polyethylene (Si-f-PO; Si-f-PE) are as follows. Using 0.14 wt% of an alkyl-substituted aryl sulfonic acid (HEC), 100% high temperature creep (150 °C, 0.2 MPa) is achieved in 5 days and 80% high temperature creep (150 °C, 0.2 MPa) is achieved in 6 days. In comparison, with 0.14 wt% of DBTDL alone, 100% high temperature creep (150 °C, 0.2 MPa) is achieved in 13 days and 80% high temperature creep (150 °C, 0.2 MPa) is achieved in 18 days.
[0071] HEC is selected from any one of (i) to (iv): (i) a Bronsted acid, (ii) a Bronsted base, (iii) a Lewis acid excluding DBTDL, and (iv) a Lewis base. HEC can be either (i) or (iii), or alternatively either (ii) or (iv).
[0072] In one embodiment, HEC is a Bronsted acid, which can be a sulfonic acid of the formula RSO3H, where R is (C1 - C 10 ) alkyl, (C6 - C 10 ) aryl, (C1 - C 10 ) alkyl-substituted (C6 - C 10)aryl, or (C6~C 10 ) Aryl substitution (C1-C 10 ) an alkyl or blocked sulfonic acid, which is prepared in situ from the sulfonic acid.
[0073] The sulfonic acid may be a hydrophobic sulfonic acid having a solubility of less than 0-0.1 g / mL in pH 7.0 distilled water at 23°C after 24 hours. The sulfonic acid may be methanesulfonic acid, benzenesulfonic acid, alkyl-substituted arylsulfonic acid, alkylbenzenesulfonic acid (e.g., 4-methylbenzenesulfonic acid, dodecylbenzenesulfonic acid, or dialkylbenzenesulfonic acid), naphthalenesulfonic acid, or alkylnaphthalenesulfonic acid.
[0074] In one embodiment, the highly efficient silanol condensation catalyst is an aromatic sulfonic acid catalyst. A non-limiting example of an aromatic sulfonic acid catalyst is a polysubstituted aromatic sulfonic acid (PASA) catalyst. The PASA catalyst has the formula HSO3Ar-R 3 (R 4 ) m It has the structure described by, in the formula, m is 1 to 3, R 3 (CH2) z CH3, z is between 0 and 3. Each R 4 R is independent of R 3 It is the same as, or different from, Ar is the aromatic part.
[0075] In further embodiments, the PASA catalyst is of the formula HSO3Ar-R 3 (R 4 ) m It has the structure described by, in the formula, m is between 0 and 3. R 3 (CH2) z CH3, and z is greater than 20. Each R 4R is independent of R 3 It is the same as, or different from, Ar is the aromatic part.
[0076] In one embodiment, the aromatic portion is a heterocyclic (e.g., pyridine, quinolone) or a non-heterocyclic (e.g., benzene or naphthalene).
[0077] In one embodiment, the value of z is 15, or 30, or 45 to 55, or 65, or 80. In further embodiments, this value is 15 to 80, or 30 to 65, or 45 to 55. When the value of z is greater than 20, PASA comprises α-olefin sulfonates, alkane sulfonates, isethionates (e.g., ethers or esters of 2-hydroxyethylsulfonic acid, also known as isethionic acid), and propanesulfone derivatives (e.g., oligomers or copolymers of acrylamidepropanesulfonic acid).
[0078] In one embodiment, HEC is a component of the masterbatch. HEC is present in the masterbatch in amounts up to 0.5, 1, 1.5, 2 to 2.5, 3.5, 5, 10, 20, 30, 40, or 50% by weight. In further embodiments, HEC is present in the masterbatch in amounts of 0.5 to 50% by weight, 1 to 30% by weight, 2 to 10% by weight, or 1.5 to 3.5% by weight. Non-limiting examples of HEC masterbatches are SI-LINK® AC DFDA-5488 NT polyethylene and SI-LINK® AC DFDB-5418 BK EXP1, each of which is composed of Brønsted acid.
[0079] In one embodiment, HEC is present in amounts ranging from 0.03, 0.05, 0.07, 0.1, 0.13, 0.15, 0.2, 0.5, 1, 2, 3, 4, or 4.5 to 6-7, 8, 10, or 12% by weight, based on the total weight of the polymer composition. In further embodiments, HEC is present in amounts ranging from 0.03-12% by weight, 0.05-8% by weight, 0.10-6% by weight, 0.03-0.20% by weight, or 0.05-0.15% by weight, based on the total weight of the polymer composition.
[0080] In one embodiment, the HEC masterbatch comprises one or more additives. Non-limiting examples of additives suitable for the HEC masterbatch include antioxidants (e.g., bis(4-(1-methyl-1-phenylethyl)phenyl)amine; 2,2'-thiobis(2-t-butyl-5-methylphenol; 2,2'-thiobis(6-t-butyl-4-methylphenol; tris[(4-tert-butyl-3-hydroxy-2,6-dimethylphenyl)methyl]-1,3,5-triazine-2,4,6-trione; pentaerythritol tetrakis(3-(3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl)propionate; distearyl thiodipropionate) Examples include thiodipropionate ("DSTDP"); dilaurylthiodipropionate; or 2',3-bis[[3-[3,5-di-tert-butyl-4-hydroxyphenyl]propionyl]]propionohydrazide), colorants (e.g., carbon black), UV stabilizers (e.g., N,N'-bisformyl-N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-hexamethylenediamine), titanium dioxide, zinc oxide, and metal deactivators (e.g., oxalylbis(benzylidene)hydrazide (OABH)).
[0081] HEC promotes crosslinking and moisture curing of foam compositions.
[0082] In one embodiment, HEC is blended with DBTDL.
[0083] HEC may consist of two or more embodiments disclosed herein. D. Permeability modifiers
[0084] The process involves providing a permeability modifier. As used herein, the term “permeability modifier” is a compound or composition that reduces the permeability of a blowing agent in a given polyolefin such that the blowing agent permeates the foam made of the polyolefin at approximately the same rate as air diffuses. This results in a foam with desirable (required) dimensional stability. Without a permeability modifier, blowing agents such as isobutane permeate polyolefin foams faster than air permeates. This can lead to dimensional instability of the foam, particularly at low foam densities, resulting in substantial foam shrinkage (leading to deterioration of foam properties). A non-limiting example of a suitable permeability modifier is C 10 ~C 24 Examples include fatty acid amides and esters. Such permeability modifiers are found in U.S. Patents 3,644,230 and 4,214,054. Esters can also reduce static electricity during and after foam production, which is another desirable attribute (especially when flammable gases such as isobutane are used as physical blowing agents). Most preferred permeability modifiers include stearyl stearamide, glycerol monostearate, glycerol monobehenate, and sorbitol monostearate. When used, such permeability modifiers are typically used in amounts ranging from 0 to 10% by weight of the polymer composition.
[0085] In one embodiment, the permeability modifier is a fatty acid ester. The fatty acid ester has an alpha-monoester (or monoglyceride) content in the range of 30-99%, 40-95%, or 50-90%. In a further embodiment, the permeability modifier is glycerol monostearate.
[0086] In one embodiment, the permeability modifier (e.g., glycerol monostearate) is a component of the masterbatch. In one embodiment, the permeability modifier (e.g., glycerol monostearate) is present in amounts up to 0.5, 1, 1.5, 2 to 2.5, 3.5, 5, 10, 20, 30, 40, 50% by weight, or 60% by weight. In further embodiments, the permeability modifier (e.g., glycerol monostearate) is present in the masterbatch in amounts of 0.5 to 60% by weight, or 1 to 50% by weight, 2 to 30% by weight, or 5 to 20% by weight.
[0087] In one embodiment, the permeability modifier (e.g., glycerol monostearate) is a component of the silane-functionalized olefin polymer. In one embodiment, the permeability modifier is present in the silane-functionalized olefin polymer in amounts up to 0.01, 0.05, 0.1, 0.2, 0.5, 1, 5, 10 to 15, 25, or 40% by weight. The weight percentage is based on the total weight of the silane-functionalized olefin polymer.
[0088] In one embodiment, the permeability modifier (e.g., glycerol monostearate) is present in an amount of 0.01, 0.1, 0.2, 0.3, or 0.5 to 1.0, 2.0, or 5.0% by weight, based on the total weight of the polymer composition. In further embodiments, the permeability modifier (e.g., glycerol monostearate) is present in an amount of 0.01 to 5.0, 0.1 to 2.0, or 0.2 to 2.0% by weight, based on the total weight of the polymer composition.
[0089] The permeability modifier may consist of two or more embodiments disclosed herein.
[0090] This process includes providing (A) a silane-functionalized olefin polymer, (B) an optional non-silane-functionalized polyolefin, (C) a high-efficiency silanol condensation catalyst, and (D) a permeability modifier under extrusion conditions at a temperature of 50°C to 250°C, and (E) optionally, a scorch inhibitor. As used herein, the term “extrusion conditions at a temperature of 50°C to 250°C” includes (i) a process occurring in one or more extruders or other suitable melt processing equipment, (ii) providing a polymer composition in a flowable state by heating the components and simultaneously blending them homogeneously, or by other means, to a temperature range of 50°C to 250°C, and (iii) introducing a blowing agent into the polymer composition at a temperature and pressure sufficient to homogeneously dissolve and disperse the blowing agent to produce a foamy composition without significant expansion. The extrusion conditions include a temperature of 50°C to 250°C and a pressure of 0.1 to 70 MPa, or 1 to 50 MPa, or 2 to 30 MPa. The extruder may consist of one or more extruders, each having one or more temperature control zones (i.e., zones).
[0091] The components are added to the extruder inlet in solid or liquid form. Any liquid component can be incorporated into one or more solid components before being added to the extruder. Alternatively, liquid components(s) can be injected into the extruder.
[0092] In one embodiment, the process involves heating components (A), optional (B), (C), (D), and optional (E) in one or more extruders at a temperature of 140°C to 250°C, or 150°C to 230°C, or 160°C to 220°C, or 170°C to 200°C, or 160°C to 190°C, and at a pressure of 0.1 to 70, or 0.5 to 60, or 1 to 50, or 2 to 40, or 3 to 30, or 4 to 20, or 6 to 10 megapascals (MPa), and blending them simultaneously to form a polymer composition. The polymer composition is in a flowable state and is also known as an extruded product. E. Physical foaming agents
[0093] This process involves introducing a physical blowing agent into a polymer composition in an extruder under extrusion conditions of 50°C to 250°C to form a foamed composition. As used herein, the term “physical blowing agent” means a compound or composition that is sufficiently soluble in the polymer composition under those conditions, is dissolved in the polymer composition under extrusion conditions, and (ii) comes out of the solution under the conditions (temperature, pressure) encountered during the formation of the foamed composition when the foamed composition exits the die. The physical blowing agent is added to the polymer composition under extrusion conditions to form a foamed composition. As used herein, the term “foamed composition” means a mixture of the polymer composition and the physical blowing agent under extrusion conditions.
[0094] In one embodiment, the physical blowing agent is added to the polymer composition downstream of the extruder inlet.
[0095] Extrusion conditions at temperatures of 50°C to 250°C include sufficiently high pressure to (i) prevent the foaming agent from expanding the polymer composition and / or foaming composition in the extruder or other suitable melting equipment, and (ii) allow for homogeneous dispersion of the foaming agent within the polymer composition. In one embodiment, the extrusion conditions include a temperature of 140°C to 200°C and a pressure of 1.40 to 3.00 MPa, or a temperature of 150°C to 190°C and a pressure of 1.80 to 2.80 MPa, or a temperature of 160°C to 180°C and a pressure of 2.20 to 2.60 MPa.
[0096] A non-limiting example of a suitable physical blowing agent is C 1~6 Hydrocarbons, such as acetylene, propane, propene, butane, butene, butadiene, isobutane, isobutylene, cyclobutane, cyclopropane, ethane, methane, ethene, pentane, pentene, cyclopentane, pentene, pentadiene, hexane, cyclohexane, hexene, and hexadiene, C 1~5 Organic halogens, C 1~6 Alcohol, C 1~6 Ether, C 1~5 Ester, C 1~5Examples include amines, alcohols, ammonia, nitrogen, carbon dioxide, water, neon, helium, and combinations thereof.
[0097] In one embodiment, the physical blowing agent is one or more of n-butane, isobutane, n-pentane, isopentane, neopentane, carbon dioxide, ethanol, and 1,1-difluoroethane (HFC-152a).
[0098] In one embodiment, the physical blowing agent is isobutane or carbon dioxide. In a further embodiment, the physical blowing agent is a mixture (combination) of isobutane and carbon dioxide.
[0099] In one embodiment, the physical blowing agent is isobutane. Isobutane is present in amounts up to 0.5, 1, 2, 5, 8, 9 to 11, 12, 15, 20, 25, or 30% by weight, based on the total weight of the foaming composition. In further embodiments, the physical blowing agent (e.g., isobutane) is present in amounts of 0.5 to 30% by weight, 2 to 25% by weight, 5 to 20% by weight, or 8 to 15% by weight, based on the total weight of the foaming composition.
[0100] The physical blowing agent may consist of two or more embodiments disclosed herein.
[0101] In one embodiment, a chemical blowing agent is used, and one or more physical blowing agents are produced by thermal decomposition in the process. Examples of chemical blowing agents include (but are not limited to) azodicarbonamide, azodiisobutyronitrile, barium azodicarboxylate, N,N'-dimethyl-N,N'-dinitrosoterephthalamide, and benzenesulfonhydrazide, 4,4-oxybenzenesulfonyl semicarbazide, as well as p-toluenesulfonyl semicarbazide, trihydrazinotriazine, and mixtures of citric acid and sodium bicarbonate. Examples of chemical blowing agents are various products sold under the trade name Safoam® (product of Reedy International; Reedy Chemical Foam).
[0102] This process involves cooling the foaming composition to a foaming temperature that is less than 10°C and greater than 10°C of Tm1 (the melting temperature of the silane-functionalized olefin polymer (A)). The applicant has unexpectedly discovered that providing 5% by weight or more of a silane-functionalized olefin polymer, an optional non-silane-functionalized polyolefin (B), HEC (C), a permeability modifier (D), and an optional scorch inhibitor (E) allows for a wide temperature range for the foaming temperature in extrusion foaming—namely, a temperature range of up to 20°C (±10°C of Tm1).
[0103] In one embodiment, the foaming temperature is ±10°C of Tm1, or ±8°C of Tm1, or ±5°C of Tm1, or ±3°C of Tm1.
[0104] This process includes pushing a foaming composition out of an extruder outlet die at a foaming temperature to form a foamed composition. This process further includes moisture curing the foamed composition under ambient conditions to form a crosslinked foamed composition. It is understood that the humidity may be adjusted to 0% to 100%, or 10% to 90%, or 20% to 80%, or 30% to 70% during moisture curing. The crosslinked foamed composition has a density of 0.010 g / cm³ (g / cc) to 0.200 g / cc and a gel content of 5% to 100%. The foaming temperature is within a temperature range in which (i) foam collapse and (ii) freeze-off do not occur during the formation of the foamed composition. The foaming temperature may be equal to, greater than, or less than the melting temperature of the silane-functionalized olefin polymer (A) or the non-silane-functionalized polyolefin (B).
[0105] In one embodiment, the process includes foaming at a foaming temperature of 50°C to 180°C, or 70°C to 160°C, or 90°C to 140°C, or 100°C to 130°C, or 100°C to 120°C, or 100°C to 110°C, or 105°C to 118°C.
[0106] In one embodiment, the melting temperature, Tm1, of the silane-functionalized olefin polymer (A) is 102°C to 112°C, and the foaming temperature is ±10°C of Tm1, or 92°C to 122°C.
[0107] In one embodiment, the melting temperature, Tm1, of the silane-functionalized olefin polymer (A) is 106°C to 108°C, and the foaming temperature is ±10°C of Tm1, or 96°C to 118°C.
[0108] In one embodiment, the melting temperature, Tm1, of the silane-functionalized olefin polymer (A) is 106°C to 108°C, and the foaming temperature is ±5°C of Tm1, or 101°C to 113°C.
[0109] This process involves forming a cross-linked foam composition having a density of 0.010 grams / cubic centimeter (g / cc) to 0.200 g / cc and a gel content of 5% to 100%. In one embodiment, the process involves forming a cross-linked foam composition having a density of 0.010 to 0.200 g / cc, or 0.015 to 0.100 g / cc, or 0.020 to 0.080 g / cc, or 0.030 to 0.070 g / cc and a gel content of 5% to 100%, or 10% to 95%, or 20% to 90%, or 30% to 80%, or 40% to 70%.
[0110] In one embodiment, the process includes forming a crosslinked foam composition having one, some, or all of the following properties: (i) Densities of 0.010 to 0.200 g / cc, or 0.015 to 0.100 g / cc, or 0.020 to 0.080 g / cc, or 0.030 to 0.070 g / cc, and / or (ii) Gel content of 5% to 100%, or 10% to 95%, or 20% to 90%, or 30% to 80%, or 40% to 70%, and / or (iii) A number of bubbles ranging from 4 to 60 bubbles per 12.7 mm, or from 5 to 40 bubbles per 12.7 mm, or from 7 to 20 bubbles per 12.7 mm, or from 5 to 7 bubbles per 12.7 mm, and / or (iv) Bubble diameters of 0.05 mm to 15 mm, or 0.07 to 10 mm, or 0.1 mm to 5.0 mm, or 0.5 mm to 4.0 mm, or 0.3 mm to 3.0 mm, or 0.5 mm to 2.0 mm, or 1.0 mm to 3.0 mm, and / or (v) Open bubbles, and / or (vi) Closed cell.
[0111] Foaming is achieved when the foaming composition exits the extruder die into a region of lower pressure and ambient conditions. In one embodiment, the process includes pushing or conveying the foaming composition through an exit die after a cooled extruder or other suitable melting equipment, forming the foaming composition as it exits the die to form a foamed composition, and moisture-curing the foamed composition to form a crosslinked foamed composition. Because the pressure outside the exit die is lower than the extruder pressure, the foaming composition experiences a pressure drop as it is pushed outward through the exit die. This pressure drop causes the physical foaming agent to expand the foaming composition, pushing it through the exit die and resulting in foam formation. In other words, the pressure outside the exit die is lower than the pressure at which the foaming composition is maintained in the extrusion process before being pushed through the exit die. The pressure outside the exit die can be atmospheric pressure, superatmospheric pressure, or low atmospheric pressure (vacuum).
[0112] In one embodiment, the extruder pressure immediately before the foaming composition exits the outlet die is 0.1, or 0.5, or 1, or 2, or 3 to 4, or 6, or 8, or 1, or 20, or 30, or 40, or 50, or 60, or 70 MPa. In a further embodiment, the extruder pressure immediately before the foaming composition exits the outlet die is 0.1 to 70 MPa, or 0.5 to 50 MPa, or 1 to 30 MPa, or 2 to 10 MPa, or 3 to 6 MPa.
[0113] In one embodiment, the process is an accumulation extrusion process and apparatus, as found in U.S. Patents No. 4,323,528 and No. 5,817,705. This apparatus, commonly known as an "extruder-accumulator system," can operate the process intermittently rather than continuously.
[0114] In one embodiment, a foam composition is formed in a bonded chain form by extruding it through a multi-orifice die. The orifices are positioned such that contact occurs between adjacent flows of molten extruded material during the foaming process, and the contact surfaces adhere to each other with sufficient adhesive force to result in a single foam structure. The flows of molten extruded material exiting the die preferably foam, bond together, and adhere to each other in the form of strands or profiles that form a single structure. Preferably, the bonded individual strands or profiles should remain bonded together in a single structure to prevent delamination of the strands under such stress during the preparation, molding, and use of the foam. Apparatus and methods for producing foam structures in the form of bonded strands are found in U.S. Patents No. 3,573,152 and No. 4,824,720.
[0115] In one embodiment, the foam composition is formed into foam beads suitable for molding into an article. Teachings for producing foam beads can be found in U.S. Patent No. 6,800,669(B2).
[0116] This process involves forming a crosslinked foam composition. Photocrosslinking (polymer chain coupling) may or may not occur under extrusion conditions at temperatures of 50°C to 250°C. However, crosslinking mainly occurs under ambient conditions after the foam composition exits the exit die, and the formed foam composition is in a solid state. Once exiting the exit die, crosslinking occurs because the foam composition hardens under ambient conditions, forming a crosslinked foam composition having a density of 0.010 g / cc to 0.200 g / cc and a gel content of 5% to 100%. Crosslinking occurs when the hydrolysis of alkoxysilane groups in Si-f-PO generates silanol moieties that condense to form siloxane bonds. HEC catalyzes the hydrolysis of alkoxysilane groups and the condensation of the resulting silanol groups, thus promoting crosslinking of the foam composition to form a crosslinked foam composition.
[0117] Moisture curing of the foam composition can be carried out under conditions other than ambient conditions. In one embodiment, moisture curing is carried out at a temperature of 36°C to 95°C, or 51°C to 95°C, a relative humidity of 5%RH to 100%RH, and a pressure of 0.5 atmospheres to 1.5 atmospheres to form a crosslinked foam composition.
[0118] In one embodiment, the process involves forming a plurality of channels (or perforations) in the foam composition. The channels extend from the surface into the foam and are non-directional with respect to the longitudinal extension of the foam. The channels can (i) increase the rate of gas-phase exchange between air and the physical blowing agent, and (ii) reduce the time required to cure or crosslink the foam composition. Perforations promote more rapid diffusion of moisture to result in complete crosslinking. The foam composition is cured under ambient conditions over durations of up to 0.2, or 0.5, or 1, or 2, or 3, or 5 to 7, or 10, or 15, or 21, or 30, or 45, or 60, or 90, or 120, or 150, or 180 days to form a crosslinked foam composition having a density of 0.010 to 0.200 g / cc and a gel content of 5% to 100%.
[0119] In one embodiment, hydroxyl-terminated polydimethylsiloxane (PDMS) may be incorporated into the formulation as a means to promote crosslinking and as a means independent of the need for foam curing in a wet or aquatic environment.
[0120] In one embodiment, crosslinking occurs as the foaming composition is pushed out of or through the exit die.
[0121] In one embodiment, crosslinking occurs after the foaming composition has been pushed out of the exit die.
[0122] In one embodiment, crosslinking occurs during the cooling of the foam composition, during the cooling of the foam composition, and in combination thereof.
[0123] The degree or amount of crosslinking present in a crosslinked foam composition depends on the amount of Si-f-PO, the amount of HEC present in the polymer composition, and the amount of copolymerized or grafted alkoxysilane in the Si-f-PO. A higher degree of crosslinking (gel content of 50% to 100%) improves properties such as the upper limit of the use temperature and compression set of the crosslinked foam composition. A lower degree of crosslinking (gel content of 5% to 49%) increases the melt strength of the foamed composition and, preferably, allows for a wider foaming temperature range for producing foam compositions with various open-cell contents (0%, or greater than 0%, up to 100%).
[0124] In one embodiment, the process includes adding a scorch inhibitor to the polymer composition. As used herein, the term “scorch inhibitor” refers to a compound or composition that prevents excessive polymer bonding or crosslinking during melt extrusion or processing (heating and / or cooling processes) before the foam composition hardens. For the purposes of this disclosure, the scorch inhibitor may also be referred to as a “scorch retarder” or “moisture scavenger.” In one embodiment, the scorch inhibitor is added to one or more solid components before the polymer composition is blended.
[0125] Non-limiting examples of suitable scorch inhibitors include alkylalkoxysilanes and combinations thereof. Non-limiting examples of alkylalkoxysilanes include octyltriethoxysilane, octyltrimethoxysilane, and hexadecyltrimethoxysilane.
[0126] In one embodiment, the scorch inhibitor is octyltriethoxysilane. The scorch inhibitor is present in an amount of 0, 0.01, 0.03, 0.05, 0.1, or 0.5 to 1.0, 2.0, or 5.0% by weight, based on the total weight of the foaming composition. In further embodiments, the scorch inhibitor is present in an amount of 0% by weight, or 0.01 to 5.0% by weight, or 0.1 to 2.0% by weight, or 0.5 to 2.0% by weight, based on the total weight of the polymer composition.
[0127] In one embodiment, the process involves adding a bubble nucleating agent to a polymer composition. The bubble nucleating agent promotes the formation of more foam bubbles, resulting in smaller bubble diameters and higher bubble densities. Higher bubble densities correlate with smaller sized foam bubbles. In one embodiment, the bubble nucleating agent is added to the solid components before the polymer composition is formed.
[0128] In one embodiment, the nucleating agent is talc, calcium carbonate, or a chemical blowing agent. In a further embodiment, the nucleating agent is talc.
[0129] This process includes residence time. As used herein, the term “residence time” is the time taken from (i) the addition of solid components to the extruder inlet to (ii) the pushing of the foaming composition through the exit die. Residence time applies to a combination of various melting processes of heating, foaming agent addition, cooling, an optional holding zone before the die (such as in an accumulation extrusion process), and pushing through the exit die. Residence time is measured from the addition of solid components to the extruder inlet up to the exit die and is the time required for the foaming composition to begin exiting the exit die. In one embodiment, residence time is 5 minutes to 80 minutes, or 6 minutes to 70 minutes, or 8 minutes to 60 minutes, or 10 minutes to 40 minutes, or 12 minutes to 30 minutes. In one embodiment, a complete transformation from a single foaming composition may require a maximum residence time of 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 times.
[0130] In one embodiment, the process described herein is a continuous process. The continuous process includes, but is not limited to, (i) adding a solid component to the extruder inlet, (ii) forming a polymer composition under extrusion conditions, (iii) introducing a physical blowing agent under melting conditions, (iv) cooling the foaming composition, and (v) pushing the foaming composition through an exit die to form a foamed composition.
[0131] The process involves forming a crosslinked foam composition containing open-cell or closed-cell or a combination thereof.
[0132] In one embodiment, the process includes forming a cross-linked foam composition containing open cells.
[0133] In one embodiment, the process includes forming a crosslinked foam composition containing closed cells.
[0134] In one embodiment, the process includes forming a crosslinked foam composition containing both open-cell and closed-cell foam. The crosslinked foam composition has 0% to 30% open-cell foam and the opposite amount of closed-cell foam, or 100% to 70% closed-cell foam. In another embodiment, the process includes forming a crosslinked foam composition having 30% to 80% open-cell foam and the opposite amount of closed-cell foam, or 70% to 20% closed-cell foam.
[0135] In one embodiment, the silane-functionalized olefin polymer is an ethylene / silane copolymer having a Tm1 of 106°C to 110°C, and the process comprises foaming at a foaming temperature of 106°C to 118°C to form a foamed composition, and moisture curing under ambient conditions to form a crosslinked foamed composition having an ethylene / silane copolymer present in an amount of 5 to 99% by weight, or 9 to 95% by weight, or 30 to 93% by weight, or 60 to 99.5% by weight, or 80 to 99% by weight, or 92 to 97% by weight, based on the weight of the composition. The crosslinked foamed composition has one or both of the following properties: (i) Densities of 0.010 g / cc to 0.200 g / cc, or 0.015 g / cc to 0.100 g / cc, and / or (ii) The composition has a gel content of 5% to 100%, or 10% to 95%, and does not contain non-silane functionalized polyolefin (B).
[0136] In one embodiment, the polymer composition comprises (A) 5% to 10% by weight of an ethylene / silane copolymer having a Tm1 of 106°C to 110°C, (B) a non-silane-functionalized polyolefin which is LDPE having a Tm2 of 80% to 90% by weight, wherein Tm2 is greater than Tm1, and (C) 0.03 to 12.0% by weight of HEC. The process comprises foaming at a foaming temperature of less than 10°C to greater than 10°C of Tm2 to form a foamed composition, and forming a crosslinked foamed composition having a density of 0.015 g / cc to 0.100 g / cc and a gel content of 10% to 95%. In a further embodiment, the Tm2 for LDPE is 111°C to 116°C, and the process comprises foaming at a foaming temperature of 111°C to 121°C.
[0137] In one embodiment, the process involves adding one or more additives to a polymer composition, a foaming composition, or a combination thereof. Non-limiting examples of suitable additives include inorganic fillers, pigments, antioxidants, acid scavengers, UV absorbers, flame retardants, processing aids, extrusion aids, antistatic agents, other thermoplastic polymers, hydroxyl-terminated polydimethylsiloxanes (PDMS), and combinations thereof.
[0138] The foaming composition can be used to form extruded thermoplastic polymer foams, or expandable thermoplastic foams, expandable thermoplastic foam beads, and molded articles formed by the expansion, bonding, and / or welding of foams and / or beads.
[0139] Crosslinked foam compositions can take any known physical form, such as extruded sheets, rods, planks, films, and profiles. Crosslinked foam compositions can also be formed by molding expandable beads into the aforementioned forms or any other forms.
[0140] Crosslinked foam compositions can be used in applications including those listed in U.S. Patent No. 6,800,669(B2). Non-limiting examples of applications include cushion packaging, sports and recreation products, egg cartons, meat trays, building structures, acoustic insulation liners, pipe insulation, gaskets, vibration pads, luggage liners, desk pads, shoe soles, gymnastics mats, greenhouse insulation blankets, case inserts, absorbent foams (e.g., for purifying applications such as health and hygiene), and display foams. Non-limiting examples of building structure applications include exterior wall cladding (home insulation), roofs, foundation insulation, and residential underlayment. Further applications of the foam compositions include refrigeration, buoyancy applications (e.g., bodyboards, floating docks, and rafts), and insulation for various floral and craft applications.
[0141] In one embodiment, the crosslinked foam composition has a thickness or diameter of 0.5 mm to 5000 mm, or 1.0 mm to 3000 mm, or 5 mm to 2000 mm, or 10 to 1000 mm, or 25 mm to 500 mm. The crosslinked foam composition may be formed by laminating two or more foam layers or at least one foam layer and at least one polymer layer.
[0142] Some embodiments of this disclosure are described in detail below, without limitation, as examples. [Examples]
[0143] The raw materials used in the Inventive Example (IE) and Comparative Sample (CS) are detailed in Table 1 below.
[0144] A high-efficiency condensation catalyst (HEC) masterbatch is prepared in a 420 mL BRABENDER mixing bowl equipped with a cam rotor. The raw materials are used in an amount sufficient to fill the mixing bowl to 70 percent capacity. The mixing bowl is heated to 160°C and the rotor speed is set to 25 rotations per minute (rpm). The carrier resin is a non-silane-functionalized polyolefin. Half of the carrier resin is added to the preheated bowl and allowed to fluidize until a complete melt is formed. The silanol condensation catalyst (e.g., sulfonic acid) is slowly added and incorporated into the carrier resin melt. Antioxidants and other additives are then added. The rotor speed is increased to 40 rpm and the mixture is allowed to fluidize for 5 minutes. The mixture is removed from the mixing bowl and cold-pressed for 5 minutes under a load of 0.689–1.38 MPa (100–200 pounds / square inch (psi)). The plaque is cut into several pieces and fed into a BRABENDER model Prep Mixer / Measurement Head laboratory electric batch mixer equipped with a 24:1 L / D extruder, and extruded at a screw speed of 40 rpm using a 20 / 40 / 20 / 40 / 20 mesh screen pack and a flat set temperature profile of 160°C across zones 1, 2, and 3, as well as the die. The resulting strand extrudes are ground in a Wiley mill to produce an HEC masterbatch as pellets. [Table 1]
[0145] The foam composition is prepared in a tandem extrusion system having a mixing extruder and a cooling extruder supplied by the mixing extruder. The mixing extruder is a co-rotating twin-screw extruder with a 34 mm diameter screw specially configured to ensure good mixing of the polymer composition and the blowing agent while forming the foamable composition. The mixing extruder is operated at a set temperature of 180°C and a screw speed of 55 rpm across all zones, with a current of 10 amperes (amp).
[0146] The cooled extruder is a single-screw extruder with a 40 mm diameter screw. The barrel and die temperatures of the cooled extruder are controlled between four zones using a separate oil heater. Zones 1 and 2 are operated at set temperatures of 129°C and 116°C, respectively. The set temperature of Zone 3 is the foaming temperature of the foamed composition. The cooled extruder is operated at a screw speed of 22 rpm and 7 amps. A 3 mm diameter rod die is mounted at the end of the cooled extruder. The die temperature is maintained between 20°C and 20°C higher than the higher of Tm1 or Tm2.
[0147] The components of the polymer composition are dry-blended and then fed into the inlet of the mixing extruder through a solid metering feeder. Once complete melting of the polymer components is achieved, a blowing agent (isobutane) is injected into the mixing extruder at a rate of 20 L / D using a positive displacement pump (dual-piston HPLC pump). The polymer flow rate is maintained at 36 grams per minute (g / min). The residence time of the process from the addition of solid components to the extruder inlet to the outlet die is 12 minutes.
[0148] The resulting foam composition is moisture-cured at 23°C and 50% humidity for 150 days.
[0149] The foam compositions of comparative samples CS1 to CS3 were prepared using the raw materials listed in Table 1, according to the formulations listed in Table 2 below.
[0150] CS1 was formed from LDPE 450E at a foaming temperature of 113°C, producing a closed-cell foam with a cell diameter of 2.9 mm and a gel content of 0%. CS2 and CS3 were formed from Agility™ 1021 LDPE. CS2 and CS3 were produced as closed-cell foams at a foaming temperature of 110°C. See Table 2. In CS1, cell collapse was evident at foaming temperatures above 113°C, and in CS2 and CS3, at foaming temperatures above 110°C (not shown in Table 2). In CS1, the melting temperature at the die began to increase at foaming temperatures below 112°C, and in CS2 and CS3, at foaming temperatures below 109°C (not shown in Table 2), indicating that freeze-off had begun. These observations are consistent with the narrow foaming temperature range of 1°C previously reported for extrusion foaming of LDPE using isobutane (Journal of Cellular Plastics, Vol.35, 531-549 (1999) and Journal of Cellular Plastics, Vol.36, 397-421 (2000)). [Table 2]
[0151] The foam compositions of Invention Examples IE1 to IE15 are prepared using the raw materials listed in Table 1 according to the formulations listed in Table 3 below.
[0152] IE1 to IE10 were formed from reactor ethylene / silane copolymers. IE1 to IE8, produced at foaming temperatures of 107.8°C to 111.7°C, yielded open-cell foams or partially open-cell foams. IE9, produced at a foaming temperature of 107.2°C, yielded an open-cell foam with a density of 0.058 g / cc. IE10, formed at a foaming temperature of 106.1°C, yielded a closed-cell foam with a density of 0.044 g / cc.
[0153] IE1 to IE10 have a foaming temperature range of 106.1°C to 111.7°C.
[0154] IE11 to IE15, formed from blends of ethylene / silane copolymer and non-silane functionalized polyolefins in a reactor foaming temperature range of 111.7°C to 116.1°C, produced closed-cell foams.
[0155] The cell diameters of the cross-linked foam compositions IE9 and IE10 are 3.9 mm and 3.1 mm, respectively.
[0156] The gel content after water curing of the foam compositions for forming cross-linked foam compositions IE9, IE10, and IE15 is 74.3% by weight, 73.3% by weight, and 10.8% by weight, respectively. [Table 3]
[0157] Surprisingly, IE1 did not produce collapsed bubbles only when cooled to a foaming temperature of 111.7°C (approximately 6°C higher than Tm1). Similarly, IE15 did not produce collapsed bubbles only when cooled to a foaming temperature of 116.1°C (approximately 5°C higher than Tm2). Furthermore, the inventive examples IE1-IE10 and IE11-IE15 exhibited a wide foaming temperature range, resulting in foam compositions that were open-cell, partially open-cell, or closed-cell. The properties of IE1-IE10 and IE11-IE15 were in stark contrast to CS1-CS3, which could only foam within a narrow foaming temperature range and resulted only in closed-cell foams.
[0158] This disclosure is not limited to the embodiments and examples contained herein, but is particularly intended to include some embodiments and modified forms of those embodiments, including combinations of elements of different embodiments, to the extent that they fall within the scope of the following claims.
Claims
1. an extruder under extrusion conditions at a temperature between 50° C. and 250° C.; (A) 89% to 95% by weight of an ethylene / silane copolymer having a first melting temperature Tm1; (B) 0.03% to 12% by weight of a highly efficient silanol condensation catalyst (HEC), which is an aromatic sulfonic acid catalyst; (C) 0.1% to 2.0% by weight of a permeability modifier that is a fatty acid ester; (D) a scorch inhibitor; and providing a polymer composition comprising: introducing a physical blowing agent into said polymeric composition under said extrusion conditions to form a foamable composition; cooling the foamable composition to a foaming temperature of 106.1°C to 111.7°C; forcing the foamable composition through an exit die of the extruder to form a foam composition; moisture curing the foam composition to form a crosslinked foam composition having a density of 0.010 grams per cubic centimeter (g / cc) to 0.200 g / cc and a gel content of 5% to 100%; The process includes:
2. 10. The process of claim 1, further comprising adding a scorch inhibitor to the polymer composition prior to said introducing.
3. 10. The process of claim 1, comprising extruding at a residence time of from 5 minutes (min) to 80 min.
4. The process of claim 1 comprising forming a foam composition comprising open cells.
5. 10. The process of claim 1 comprising forming a foam composition comprising closed cells.
6. 10. The process of claim 1, comprising forming a foam composition comprising foam cells having a cell diameter of 0.1 millimeters (mm) to 5.0 mm.
7. 10. The process of claim 1 comprising forming a foam composition having a cell count of from 5 cells per 12.7 mm to 40 cells per 12.7 mm.
8. An extruder under extrusion conditions at a temperature of 50°C to 250°C, and (A) 5% to 10% by weight of an ethylene / silane copolymer having a first melting temperature Tm1; (B) 80% to 90% by weight of a non-silane-functionalized polyolefin that is a LDPE having a second melting temperature Tm2; (C) 0.03 wt. % to 12.0 wt. % of a highly efficient silanol condensation catalyst (HEC), which is an aromatic sulfonic acid catalyst; (D) 0.1% to 2.0% by weight of a permeability modifier that is a fatty acid ester; (E) a scorch inhibitor; wherein each weight percent is based on the total weight of the polymer composition; and introducing a physical blowing agent into said polymeric composition under said extrusion conditions to form a foamable composition; cooling the foamable composition to a foaming temperature of 111.7°C to 116.1°C; forcing the foamable composition through an exit die of the extruder to form a foam composition; moisture curing the foam composition to form a crosslinked foam composition having a density of 0.015 g / cc to 0.100 g / c and a gel content of 10% to 95%; The process includes:
9. The process of claim 8, wherein the process comprises foaming at a foaming temperature between 10°C below Tm2 and 10°C above Tm2.
10. The process of claim 9, wherein Tm1 is greater than Tm2, and the process comprises foaming at a foaming temperature 10°C lower than Tm1 to 10°C higher than Tm1.
11. The process of claim 9, wherein Tm2 is greater than Tm1, and the process comprises foaming at a foaming temperature 10°C lower than Tm2 to 10°C higher than Tm2.